IMPLEMENTASI TEKNOLOGI CANGGIH DALAM MENGURANGI RISIKO PELAKSANAAN KONSTRUKSI BANGUNAN GEDUNG TINGGI - Tobing, Santo Lumban (Universitas 17 Agustus 1945 Jakarta, 2024)
This research aims to explore and evaluate the implementation of advanced technologies in reducing the risks associated with high-rise building construction. The main objective of this study is to analyze the effectiveness of various technologies such as Building Information Modeling (BIM), sensors and Internet of Things (IoT), robotics, and Virtual Reality (VR) in the context of safety, health, and operational efficiency. The research methodology includes a comprehensive literature review of relevant scholarly articles and analysis of case studies from construction projects that have implemented these advanced technologies. Case studies are used to evaluate the positive impact of advanced technologies in reducing accident incidents, enhancing project coordination, and optimizing resource utilization. The findings of this research indicate that the use of BIM significantly improves interdisciplinary coordination and reduces design errors. The implementation of sensors and IoT successfully monitors real-time environmental conditions, while robotics aids in reducing risks for workers in hazardous work environments. Additionally, VR has proven effective in training workers through simulated hazardous work scenarios